2009
DOI: 10.1111/j.1365-2648.2009.05190.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hospital nurse intention to remain employed: broadening our understanding

Abstract: TitleDeterminants of hospital nurse intention to remain employed: broadening ourunderstanding.AimThis paper is a report of a study to identify nurse reported determinants of intention to remain employed and to develop a model explaining determinants of hospital nurse intention to remain employed.BackgroundA worsening shortage of nurses globally suggests that efforts must be made to promote retention of nurses. However, effective retention promotion strategies depend on understanding the factors influencing nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
217
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(244 citation statements)
references
References 43 publications
(84 reference statements)
15
217
0
9
Order By: Relevance
“…Good mentoring enhances both career success and job satisfaction (Chung & Kowolski, 2012;Gerolamo & Roemer, 2011;Perna & Lerner, 1995). This is significant as these factors have both been found to influence decisions regarding whether to remain in employment (Tourangeau et al, 2010). This resonates with previous research which found that academics with mentors have greater socio-emotional support, greater job satisfaction and had less intention of leaving the faculty in the immediate future (Wasserstein, Quistberg & Shea, 2007).…”
Section: Introductionsupporting
confidence: 85%
“…Good mentoring enhances both career success and job satisfaction (Chung & Kowolski, 2012;Gerolamo & Roemer, 2011;Perna & Lerner, 1995). This is significant as these factors have both been found to influence decisions regarding whether to remain in employment (Tourangeau et al, 2010). This resonates with previous research which found that academics with mentors have greater socio-emotional support, greater job satisfaction and had less intention of leaving the faculty in the immediate future (Wasserstein, Quistberg & Shea, 2007).…”
Section: Introductionsupporting
confidence: 85%
“…Also, it was found, that the longer the professional has been working at the institution, the higher the degree of satisfaction, in contrast with what was observed for nurses working on psychiatric wards (3) . According to international studies, nurses who reported emotional involvement in their work activities were more satisfi ed and less inclined to leave their current job (10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Non recognition and devaluation generate dissatisfaction (11) . So, being noticed and valued is satisfactory for nurses (19) .…”
Section: Discussionmentioning
confidence: 99%
“…The balance between work and family subscale measured nurses' satisfaction with control over what goes on at their work setting, opportunities for career advancement, amount of responsibilities, control on work conditions, and participation in decision-making. Nurses' plans to stay or leave were correlated to their control on work environment and availability of resources and equipment as the latter wasted their time and burned them out [27]. Multiple studies have shown correlation with control and responsibilities and job satisfaction, Mokoka et al [28] found a strong correlation with job satisfaction and intent to leave and unfair opportunities to job development [29,30] and noted a control over work included involvement in decision making and competency of work place and Takase et al [31] found that nurses were more satisfied and intended to stay when they were involved in the decision making to establish policies and patient education.…”
Section: Discussionmentioning
confidence: 99%